Handbook of chemical engineering calculations (McGraw-Hill, 1993)
The book presents step-by-step calculations methods and solutions to problems in physical and chemical properties, stoichiometry, phase equilibrium, chemical-reaction equilibrium, reaction kinetis and reactor design, flow of fluids and solids, heat transfer, distillation, absorption and stripping, extraction and leaching, crystallization, filtration, liquid agitation, size reduction, air pollution